Solanum tuberosum L: Botanical, Phytochemical, Pharmacological and Nutritional Significance - Anjum Sahair R; Sneha S; Raghu N; Gopenath TS; Murugesan Karthikeyan; Ashok Gnanasekaran; Chandrashekrappa GK; Kanthesh M Basalingappa (International Journal of Phytomedicine, 2018)
Solanum tuberosum commonly known as potato belongs to solanaceae family. The whole part of potato plant including leaves; tuber, peel and juice are used in traditional medicine. A number of pharmacological activities of potato have been reported viz. Antioxidant, anticancer, antiallergy, antibacterial, anti-inflammatory, antiobesity, anti-ulcer activity. Potato contains Phenolic acids, anthocyanin, flavonoids, vitamin B6, vitamin B3, pantothenic acid, potassium, manganese, phosphorous; copper and fibres. The medicinal properties, traditional uses, nutritional value, phytochemical constituents, taxonomy, geographic origin and distribution have been mentioned in this present review to provide collective data for multipurpose benefits.